(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Fit India Movement, initiated by the Indian government, aims to enhance health and well-being through yoga and physical fitness activities. This study investigated the effect of the Fit India Fitness Protocol (FIFP) on the cardiovascular endurance of Junior College students. It randomly selected 60 male students aged 16 to 19 from Govt Junior College, Narasannapeta, Srikakulam and assigned them to four groups, each including 15 members. Group I engaged in physical fitness exercises, Group II performed yoga, Group III participated in both physical fitness and yoga, while Group IV served as the control group. The intervention lasted 12 weeks, during which individuals in the treatment groups trained three days a week, while the control group adhered to their regular routines. We used the 2 km walk/run test as the criterion variable to evaluate the differences in cardiovascular endurance among the groups. A one-way analysis of covariance (ANCOVA) employing pre-reading cardiovascular endurance as a covariate revealed that all three treatment groups had significantly greater cardiovascular endurance compared to the control group. The Bonferroni post-hoc test indicated that the physical fitness exercise group (Group I) attained the greatest improvements in cardiovascular endurance. The data indicate that the Fit India physical fitness exercise protocol significantly improves the cardiovascular endurance along with the health and well-being of the law college students.